The Role of Parenting Style on Aggressive Behavior of Junior High School Adolescents - Manda, Darman; Darmayanti, Dyan Paramitha; St. Junaeda (Universitas Sulawesi Barat, 2025)
Aggressive behavior among junior high school students is a critical issue that negatively impacts students' social-emotional development and the learning environment at school. This article critically examines the relationship between parenting styles and adolescent aggressive behavior, highlighting the role of self-control as a mediating variable. Through a qualitative literature review of 35 relevant studies from the fields of psychology, education, and family sociology, this article finds that authoritarian and permissive parenting styles are positively correlated with aggressive tendencies. In contrast, authoritative parenting tends to protect children from deviant behavior. On the other hand, self-control was found to play a significant role in mitigating the negative influence of parenting on adolescent aggression, mainly when supported by the presence of an authoritative figure, a supportive social environment, and appropriate educational interventions. These findings underscore the significance of self-control as a mediator between parenting and aggressive behavioral responses in adolescents.